EN FACE OPTICAL COHERENCE TOMOGRAPHY AND OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY OF INNER RETINAL DIMPLES AFTER INTERNAL LIMITING MEMBRANE PEELING FOR FULL-THICKNESS MACULAR HOLES. Issue 3 (March 2020) - Navajas, Eduardo V.; Schuck, Nathan; Govetto, Andrea; Akil, Handan; Docherty, Gavin; Heisler, Morgan; Sarunic, Marinko V.; Sarraf, David
Abstract : Purpose: To quantitatively and qualitatively evaluate the microvascular and structural abnormalities associated with inner retinal dimpling after internal limiting membrane peeling for full-thickness macular holes using sequential en face optical coherence tomography (OCT) and OCT angiography. Methods: Thirteen eyes of 13 patients with idiopathic full-thickness macular holes were enrolled in the study. Patients were treated with pars plana vitrectomy, internal limiting membrane peeling, and gas tamponade. Subjects were evaluated preoperatively and at postoperative Months 1, 3, and 6. At each visit, patients underwent a comprehensive ophthalmologic examination, en face OCT and OCT angiography. The morphology and number and proportionate area of inner retinal dimples were analyzed. Vessel density of the superficial vascular complex at all visits was also measured. Results: Inner retinal dimples were identified 1 month after surgery in all cases. The number and proportionate area of inner retinal dimples significantly increased over the follow-up period ( P = 0.05). Preoperative vessel density of the superficial vascular complex was 17.9 ± 1.9 and did not change significantly over the follow-up period ( P = 0.15). Conclusion: Inner retinal dimples are identified with en face OCT as early as the first month after internal limiting membrane peeling for idiopathic full-thickness macular holes and progressively increase in number and proportionate area in the subsequent 3 to 6 months after surgery. This may be the result of progressive deturgescence of the nerve fiber layer in the postoperative period. Abstract : Inner retinal dimples were revealed with en face optical coherence tomography as early as the first month after internal limiting membrane peeling for idiopathic full-thickness macular holes. An increase in number and proportionate area of inner retinal dimples was observed postoperatively, a phenomenon possibly related to the progressive deturgescence of the nerve fiber layer.